Práticas de alfabetização e letramento nos anos iniciais do ensino fundamental - SANTOS, Maila Fernanda Rosa dos (2021)
Literacy, conceived as a restricted system of acquisition related only to the act of decoding and coding, begins to suffer criticism and disturb teachers, who come to understand that just knowing how to read and write is not enough for people to realize what literate practices in today's society require them. In this sense, the present study aims to understand how the practices of literacy are organized and developed in the early years of elementary school at the Municipal School of Elementary School. Julia Pictures Peinado. Thus, seeking to know the conception of literacy that guides the practices of literacy teachers and to understand in what sense these approach or distance from the epistemological perspective of literacy, as well as relate to the curricular proposal of the school. The research focuses on a qualitative approach of ethnographic nature, for collecting empirical data was used participant observation and questionnaires to two elementary school teachers, being 1st and 4th grade. The results of this research showed that the teachers' practices are articulated with the school's curricular proposal; however, their practices, while approaching literacy, tend to distance themselves, because the old model of literacy, concentrated only on reading and writing. writing is still very present in the school context.